Performance Analysis in Quantitative Traits of Local Chickens (Gallus gallus sp.) In Kediri Regency East Java - Eka Nurwahyuni; A. R. I. Putri; N. Febrianto; M. A. Marom; R. F. Azhar (Universitas Bengkulu, 2023)
This study aimed to determine the phenotypic diversity of the quantitative characteristics and the results of the analysis of kinship relationships of local chickens in Kediri by using 60 adult male local chickens. Data were obtained by directly observing the quantitative characteristics according to the variables: head length, chest-length, wing length from right to left, shank length, back length, neck circumference, and chest circumference. The results showed that the majority of phenotypes were from local chickens in Kediri, consisting; of a wing length of 52.1cm, head length of 8.58cm, chest length of 28.8cm, shank length of 12.4cm, a back length of 25.35cm, neck circumference 13.98cm, and chest circumference 40.4cm. It can be concluded that local chickens in Kediri have a variety of quantitative characteristics, and the average results for each sub-district are not much different from the others. It is hoped that the results of this study can be used as primary data for further research to determine the quality and superior breeding selection.